2021
DOI: 10.1016/j.psj.2021.101196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a probiotic-fermented herbal blend on the growth performance, intestinal flora and immune function of chicks infected with Salmonella pullorum

Abstract: Salmonella pullorum is a highly pathogenic bacteria in poultry industry. However, antibiotics were restricted in many countries because of the increasing risk of antibiotic resistance, Therefore, an environmental friendly and effective alternative strives to be developed. This study investigated the benefit of a probiotic-fermented herbal blend on the growth performance and gut microbiota of newborn broilers infected with S. pullorum . A total of 120 one-day-old dwarf male chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 41 publications
6
34
0
Order By: Relevance
“…The administration of L. rhamnosus reduced the mortality rate of chicks from 50.00% to 15.00% and ameliorated the body weight of Salmonella-infected chicks. These findings are consistent with previously reported studies, in which different probiotics have demonstrated the ability to reduce the mortality rate and to improve body weight gain of chicks infected with Salmonella (54)(55)(56). Additionally, our findings showed the effectiveness of L. rhamnosus in reducing the number of Salmonella colonized Liver, spleen, duodenum, cecum, and feces.…”
Section: Discussionsupporting
confidence: 93%
“…The administration of L. rhamnosus reduced the mortality rate of chicks from 50.00% to 15.00% and ameliorated the body weight of Salmonella-infected chicks. These findings are consistent with previously reported studies, in which different probiotics have demonstrated the ability to reduce the mortality rate and to improve body weight gain of chicks infected with Salmonella (54)(55)(56). Additionally, our findings showed the effectiveness of L. rhamnosus in reducing the number of Salmonella colonized Liver, spleen, duodenum, cecum, and feces.…”
Section: Discussionsupporting
confidence: 93%
“…The above results indicated that oral gavage of LB(+) combined with EA effectively enhanced the activation of the Nrf2/HO-1 pathway, effectively inhibited the ChTLR15/ChNLRP3 inflammatory pathway triggered by E. tenella , and thus provided anti-inflammatory effects. The results from the present study are consistent with those of other reports, which showed that the combination of probiotics and herbs had strong potential functions [ 35 , 36 ]. A possible explanation for the present results may be related to the following questions.…”
Section: Discussionsupporting
confidence: 93%
“…The role of the gut microbiota has attracted increasing attention, and the gut microbiota is closely related to livestock and poultry production performance [ 19 , 20 , 21 , 22 ], nutritional metabolism [ 15 , 23 ], and immune function [ 24 , 25 ]. Predecessors found through the technique of faecal microbiota transplantation that the growth performance of calves after faecal microbiota transplantation was significantly increased [ 21 ], which shows that the growth performance of gut microbiota is improved, but the mechanism of action is still unclear.…”
Section: Introductionmentioning
confidence: 99%